A-113 A Case Study: Utilization of C3 Logix in Serial Evaluation of Concussion in a Multidisciplinary Medical Setting. (28th August 2020) - R, Zill; H, Dean-Hill; M, Alcala; E, Snell; G, Getz
Abstract: Objective: C3 Logix is a concussion assessment and management system addressing patient care, return to play standards, and rehabilitation or understanding of concussion. This case study demonstrates the utility of the C3 Logix screening measure with a concussion patient in a multidisciplinary medical setting. Repeat C3 Logix screening data was compared to reported symptoms on the Post-Concussion Symptom Scale (PCSS) and interpreted by a physician in medical setting. This case highlights the comparison of C3 Logix findings and a neuropsychological profile in a young adult with history of traumatic closed head injury. Method: 25-year old, right-handed, Caucasian man with no significant medical history prior to sustaining a parenchymal hemorrhage along the left anterior inferior frontal lobe and left temporal lobe, as well as a left anterior frontal subdural hematoma in 2019. The patient reported a premorbid history of generalized anxiety with panic, and elevated emotionality post-injury. Results: Estimated premorbid verbal functioning was average, consistent with his score as predicted by demographic variables. The patient exhibited decreased concussion symptom severity and improved cognitive performance across repeat C3 Logix administrations. On comprehensive neuropsychological evaluation, he demonstrated intact performance across cognitive domains, with relative weakness consistent with localization of injury, sustained eye injury, and expected recovery duration. Conclusions: Repeat cognitive screenings were generally consistent with comprehensive neuropsychological evaluation results. This case study highlights that the C3 Logix tool should be further considered as a brief cognitive screening measure to inform treatment of traumatic head injuries within a multidisciplinary medical setting.